A little respect (for the role of common components in heuristic search) - Chen, Stephen (2006)
A search process implies an exploration of new, unvisited states. This quest to find something new tends to emphasize the processes of change. However, heuristic search is different from random search because features of previous solutions are preserved – even if the preservation of these features is a passive decision. A new parallel simulated annealing procedure is developed that makes some active decisions on which solution features should be preserved. The improved performance of this modified procedure helps demonstrate the beneficial role of common components in heuristic search